EUROPEAN AND AMERICAN PERSPECTIVES ON THE CHOICE OF LAW REGARDING CROSS-BORDER INSOLVENCIES OF MULTINATIONAL CORPORATIONS – SUGGESTIONS FOR SOUTH AFRICA - Jeanette Weideman (Potchefstroom Electronic Law Journal, 2012)
An increase in economic globalisation and international trade has amounted to an increase in the number of multinational enterprises that have debt, own assets and conduct business in various jurisdictions around the world. This, coupled with the recent worldwide economic recession, has inevitably caused the increased occurrence of multinational financial default, also known as cross-border insolvency (CBI). The legal response to this trend has, inter alia, produced two important international instruments that were designed to address key issues associated with CBI. Firstly, the United Nations Commission on International Trade Law (UNCITRAL) adopted the UNCITRAL Model Law on Cross-Border Insolvency (the Model Law) in 1997, which has been adopted by nineteen countries including the United States of America and South Africa. Secondly, the European Union (EU) adopted the European Council Regulation on Insolvency Proceedings (EC Regulation) in 2000. Both the EC Regulation and Chapter 15 adopt a “modified universalist” approach towards CBI matters. Europe and the United States of America are currently the world leaders in the area of CBI and the CBI legislation adopted and applied in these jurisdictions seems to be effective. As South Africa’s Cross-Border Insolvency Act is not yet effective, there is no local policy guidance available to insolvency practitioners with regard to the application of the Model Law. At the basis of this article is the view that an analysis of the European and American approaches to CBI matters will provide South African practitioners with valuable insight, knowledge and lessons that could be used to understand and apply the principles adopted and applied in terms of the EC Regulation and Chapter 15, specifically the COMI concept, the “establishment” concept in the case of integrated multinational enterprises and related aspects.